Epitranscriptome profiling of spleen mRNA m6A methylation reveals pathways of host responses to malaria parasite infection - Wang, Luoluo; Wu, Jian; Liu, Runzhou; Chen, Wenjun; Pang, Zhichang; Zhou, Fan; Xia, Lu; Huang, Jia; Pan, Tao; Su, Xin-zhuan; Wang, Xiaoyun (Frontiers in Immunology, 2022)
N6-Methyladenosine (m6A), the most abundant mammalian mRNA modification, has been reported to modulate various viral infections. Although it has been confirmed that RNA modifications can also modulate the replication and development of different parasites, the role of the RNA epitranscriptome in the regulation of host response post parasite infection remains to be elucidated. Here we report host spleen m6A epitranscriptome landscapes induced by different strains of the malaria parasite Plasmodium yoelii. We found that malaria infection dramatically changes host spleen m6A mRNA modification and gene expression. Additionally, malaria parasite infection reprograms host immune response pathways by regulating the m6A modification enzymes. Collectively, our study is the first characterization of host spleen m6A methylome triggered by parasite infections, and our data identify m6A modifications as significant transcriptome-wide marks during host-parasite interactions. We demonstrate that host mRNA methylation machinery can sense and respond to malaria parasite infections, and provide new insights into epitranscriptomic mechanisms underlying parasite-induced pathogenesis.